2008
DOI: 10.1128/jb.01136-08
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Salmonella enterica std Fimbrial Operon by DNA Adenine Methylation, SeqA, and HdfR

Abstract: DNA adenine methylase (dam) mutants of Salmonella enterica serovar Typhimurium grown under laboratory conditions express the std fimbrial operon, which is tightly repressed in the wild type. Here, we show that uncontrolled production of Std fimbriae in S. enterica serovar Typhimurium dam mutants contributes to attenuation in mice, as indicated by the observation that an stdA dam strain is more competitive than a dam strain upon oral infection. Dam methylation appears to regulate std transcription, rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 53 publications
3
73
0
Order By: Relevance
“…Proteins were resolved by Tris-Tricine-PAGE, using 12% gels. Conditions for protein transfer have been described elsewere (Jakomin et al 2008). Primary antibodies were anti-Flag M2 monoclonal antibody (1:5000, Sigma), anti-HA HA.11 monoclonal antibody (1:1000; Covance, Princeton, NJ), and anti-GroEL polyclonal antibody (1:20,000, Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins were resolved by Tris-Tricine-PAGE, using 12% gels. Conditions for protein transfer have been described elsewere (Jakomin et al 2008). Primary antibodies were anti-Flag M2 monoclonal antibody (1:5000, Sigma), anti-HA HA.11 monoclonal antibody (1:1000; Covance, Princeton, NJ), and anti-GroEL polyclonal antibody (1:20,000, Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Because the methylation state of critical GATC sites can control binding of RNA polymerase and transcription factors, differences in gene expression between Dam 1 and Dam À hosts usually provide evidence for transcriptional regulation (Roberts et al 1985;Kü cherer et al 1986;Blyn et al 1989;Torreblanca and Casadesus 1996;Haagmans and Van Der Woude Figure 7.-(A) Camacho and Casadesus 2002;Waldron et al 2002;Balbontin et al 2006;Jakomin et al 2008). However, several lines of evidence suggest that Damdependent regulation of hilD expression is not transcriptional: (i) a transcriptional hilDTlac fusion is expressed at similar levels in Dam 1 and Dam À hosts ( Figure 4); (ii) reduced levels of both hilD mRNA and HilD protein are, however, found in Dam À mutants ( Figures 2 and 4); (iii) reduced amounts of hilD mRNA are found in a Dam À mutants when the hilD gene is expressed from a heterologous promoter ( Figure 5); (iv) SPI-1 remains under Dam-dependent control when hilD transcription is activated by tetracycline ( Figure 5); and (v) lack of DNA adenine methylation results in hilD mRNA instability (Figure 6).…”
Section: Levels Of the Spi-1 Transcription Factorsmentioning
confidence: 99%
“…Analysis of transposon insertions showed that SeqA, a protein that binds GATC sites, repressed stdA expression (45). In contrast HdfR, a member of the LysR-like regulators, was shown to activate stdA transcription (45). Whether this activation occurs by the direct binding of HdfR to the regulatory region of the sfa operon or is due to an indirect effect is unknown.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Examination of the predicted promoter region of stdA revealed three GATC sites within a 25-bp region. Analysis of transposon insertions showed that SeqA, a protein that binds GATC sites, repressed stdA expression (45). In contrast HdfR, a member of the LysR-like regulators, was shown to activate stdA transcription (45).…”
Section: Dna Methylationmentioning
confidence: 99%
“…Mutants were grown in LB supplemented with Tet, and the T-POP promoter and also regulator gene were activated in order to achieve expression of the regulator. If the regulator were a negative regulator, depending upon tetracycline induction, inactivation of the stj fimbrial operon would be expected (7,23). Significant increases in β-galactosidase activities of the MDN20 mutant pointed out that stj fimbrial operon regulated by a positive transcriptional regulator.…”
Section: Smentioning
confidence: 99%